Fuzzy model and method for farmland fertilization planning (Selecciones Matemáticas, 2021)
Fuzzy set theory was used for modeling and fuzzy optimization methods for solving the problem of farmland fertilization considering the fuzzy constraints and costs. A method solution was proposed based on the proposals of Lai-Hwang, Leberling and Verdegay. The methodology that transforms a fuzzy objective into a multi-objective optimization problem, and these into fuzzy goals, and finally alfa-cut is used to transform it into a classic problem. The method is illustrated with an example. The solution obtained is a triple that represents a fuzzy number, which provides greater flexibility to the decision maker.
Keywords: Fuzzy linear optimization; farmland fertilization; fuzzy cost; fuzzy constraints